Hubungan Kepatuhan Sign-In Dengan Ketepatan Identifikasi Pasien Pre – Operatif Di RS Primaya Betang Pambelum - Karmitasari Yanra Katimenta; Dwi Agustian Faruk Ibrahim; Bri Yudistira (Pusat riset dan Inovasi Nasional, 2023)
Before the patient is delivered to the operating room, the sign-in action is carried out in the reception room by the health worker before the patient is escorted to the operating table, the sign-in compliance includes identifying the patient, checking the informed consent (consent sheet), checking the surgical site marking, allergy history and supporting examination documents. Every health worker will take action on pre-operative patients in the application of health workers still do not properly identify patients during routine medical / nursing actions, patient identity is mentioned by health workers, health workers do not immediately record and report the results of sign in. This study aims to determine the relationship between sign-in compliance with the accuracy of pre-operative patient identification at Primaya Betang Pambelum Hospital, Method: This type of research is correlational using Cross sectional. The technique of determining respondents using purposive sampling using the Chi Square statistical test. The sample is patients who will undergo surgery at Primaya Betang Pambelum Hospital totaling 109 respondents. Results: The results of the Chi Square statistical test that obtained p value = 0.000 or the level of significance p < 0.05 so that there is a relationship between sign-in compliance with the accuracy of pre-operative patient identification, Conclusion: There is a relationship between sign-in compliance with the accuracy of pre-operaif patient identification as evidenced by the results of p < α with a significant level of 0.05 indicating a significant and meaningful relationship between sign-in compliance with the accuracy of patient identification at Primaya Betang Pambelum Hospital.